2015
DOI: 10.6004/jnccn.2015.0133
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Venous Thromboembolic Disease, Version 1.2015

Abstract: The NCCN Guidelines for Cancer-Associated Venous Thromboembolic Disease outline strategies for treatment and prevention of venous thromboembolism (VTE) in adult patients with a diagnosis of cancer or for whom cancer is clinically suspected. VTE is a common complication in patients with cancer, which places them at greater risk for morbidity and mortality. Therefore, risk-appropriate prophylaxis is an essential component for the optimal care of inpatients and outpatients with cancer. Critical to meeting this go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 101 publications
1
114
0
10
Order By: Relevance
“…Therefore, at the present time, the author recommends that all hospitalized medical and surgical oncology patients receive thromboprophylaxis consistent with the National Comprehensive Cancer Network (NCCN) guidelines. 23 The American Society of Clinical Oncology (ASCO) guidelines recommend routine thromboprophylaxis in all hospitalized patients except for those admitted solely for a minor procedure or chemotherapy. 24 Future research initiatives should focus on demonstrating the efficacy of VTE prophylaxis in hospitalized medical oncology patients, and developing and validating cancerspecific VTE RAMs.…”
Section: What Is the Risk Of Venous Thromboembolism (Vte) In Cancer Pmentioning
confidence: 99%
“…Therefore, at the present time, the author recommends that all hospitalized medical and surgical oncology patients receive thromboprophylaxis consistent with the National Comprehensive Cancer Network (NCCN) guidelines. 23 The American Society of Clinical Oncology (ASCO) guidelines recommend routine thromboprophylaxis in all hospitalized patients except for those admitted solely for a minor procedure or chemotherapy. 24 Future research initiatives should focus on demonstrating the efficacy of VTE prophylaxis in hospitalized medical oncology patients, and developing and validating cancerspecific VTE RAMs.…”
Section: What Is the Risk Of Venous Thromboembolism (Vte) In Cancer Pmentioning
confidence: 99%
“…Additional key articles and other clinical practice guidelines 13,[15][16][17]132 on overlapping clinical questions were consulted and included. The search included meta-analyses, systematic reviews, randomised clinical trials, or non-randomised prospective or retrospective studies (in the absence of randomised clinical trials).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…(The Nordic Cochrane Centre, The Cochrane Collaboration, Copenhagen), and found that overall, compared with VKA, LMWH reduced the risks of recurrent VTE by 40% (relative risk [RR] 0.60, 95% CI 0.45‐0.80) (Figure 1A) with no difference in major bleeding (RR 1.07, 95% CI 0.65‐1.75) (Figure 1B). Several major clinical guidelines have recommended LMWH as the first line therapy for treatment of acute CAT 34, 35, 36…”
Section: Treatment Of Cancer‐associated Thrombosismentioning
confidence: 99%